2021
DOI: 10.3390/su13041835
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Tourism: A Human-Centered Approach

Abstract: The aim of this paper is to present an alternative approach to sustainable tourism-derived from the human-centered angle. In line with this assumption, when considering the principles of sustainable tourism, the opinions of all groups of tourism actors, including host communities, tourists and tourism businesses should be taken into account equally with other factors, not merely as one of many decision makers, but as the main frame of reference. The research methodology is twofold. As regards the theoretical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…A study by Dogru et al (2020) found that although improvements in the travel business have a detrimental influence on CO 2 emissions in Turkey and Canada, they basically have a certain effect on emissions from the European Union countries of Italy, Slovakia, and Luxemburg. Travel industry groups, sightseers, and travel industry networks are all together referred to as the travel industry by Butowski (2021), even if these entertainers have an equal stake in preserving reasonable travel business. According to Khan et al (2019), the impact of Coronavirus, which has decimated the tourism sector over the last two years, is also being examined.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study by Dogru et al (2020) found that although improvements in the travel business have a detrimental influence on CO 2 emissions in Turkey and Canada, they basically have a certain effect on emissions from the European Union countries of Italy, Slovakia, and Luxemburg. Travel industry groups, sightseers, and travel industry networks are all together referred to as the travel industry by Butowski (2021), even if these entertainers have an equal stake in preserving reasonable travel business. According to Khan et al (2019), the impact of Coronavirus, which has decimated the tourism sector over the last two years, is also being examined.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, in order to characterize the current condition of the infrastructure and the operation of the water transport and tourism system in the region, field studies (participant observation) were conducted in all localities on coastline of the Polish part of the lagoon, and unpublished data from the Harbor Master's Office in Elbląg (analysis of quantitative data of passengers on cruises on the Vistula Lagoon in 2007-2019) were used. As noted by Butowski [2], the combination of quantitative and qualitative analyses is the right approach to inventorying the needs of various tourism stakeholders and shaping sustainable tourism in a wide paradigm of sustainable development.…”
Section: Methodsmentioning
confidence: 99%
“…Lagoons are a specific form of surface waters whose high natural values contribute to the commercialization of their use in the form of tourism. The Vistula Lagoon has been classified as a rather capitalized lagoon among water reservoirs located in European countries [1,2]. On a national scale, it is a region of above-average importance for tourism (mainly sightseeing and recreation).…”
Section: Introductionmentioning
confidence: 99%
“…Renewable energy consumption is found to be the critical determinant of sustainable tourism development and also a decrease in the level of carbon emissions. Butowski (2021) investigates the key determinants of sustainable tourism and report that the tourists, host communities, and tourism businesses are collectively called tourism, whereas these actors have an equal stake in maintaining sustainable tourism. A qualitative survey conducted in seven different regions of Poland reveals that host communities living in the tourists' places can take maximum advantages from tourism.…”
Section: Literature Reviewmentioning
confidence: 99%